Collaborative Concept Mapping: Investigating the Nature of Discourse Patterns and Features of a Concept Map - Khoza, Hlologelo Climant; Maseko, Bob (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
Research in science education has established the significance of collaborative concept mapping as a powerful strategy in fostering conceptual learning. During such collaboration, students talk about concept map features (i.e., concepts to include, linking words, and cross-links) in constructing a joint map. The quality of the concept map produced depends on the nature of discourses that happen in these collaborative interactions. We explored the nature of discourses between pairs of biology students collaborating on concept mapping and how these discourses contribute to the enhancement of different features of the concept maps. Six students individually constructed weekly individual maps on different topics and then came together in pairs to construct a joint concept map. Their discussions during collaboration were audio-recorded. Both the individual and joint concept maps were analyzed for knowledge of breadth, knowledge of depth, and knowledge of connectedness. To analyze the discussions and understand the nature of the discourses, both deductive and inductive coding approaches were used. The coded episodes were then categorised into the nine discourse patterns identified by Fu et al. (2016). We then matched the episodes with the concept map features that were discussed. Findings indicate that the biology students’ collaboration exhibited mostly knowledge-sharing discourses when deliberating on the three features of a concept map. In turn, the number of valid concepts and propositions improved from individual to joint maps. Although the students’ discussions of cross-links were characterized by knowledge-sharing discourses, most of the joint maps did not show improvement in terms of the number cross-links. We discuss these findings and provide implications regarding the value of understanding the intricacies of discourse patterns in collaborative concept mapping.